EFFECTIVENESS OF USING THE QUIZIZZ APPLICATION IN IMPROVING GRAMMAR PROFICIENCY - Kristi, Ela (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
One of the most essential components in supporting English mastery is grammar. This study explores the effectiveness of the quizizz application in improving grammar proficiency among Informatics Engineering students at Universitas Muhammadiyah Brebes. The research responds to the growing need for engaging and effective grammar instruction through technology integration. This study used a quasi-experimental method with one-group pretest-posttest design and involved 15 students as participants. Data were collected through grammar tests and questionnaires. The results showed a substantial rise in students’ grammar scores, an increase from an average pre-test score of 66,4 to a post-test average of 78,6, with an N-Gain score of 0,40, categorized as moderate improvement. The questionnaire results revealed that most students found Quizizz engaging and helpful in identifying grammar weaknesses, improving understanding, and boosting motivation. In conclusion, the integration of Quizizz in grammar instruction positively impacts students’ learning outcomes and perceptions. The study recommends its use as a complementary instrument for language lecturers looking for enhancing learning through gamified digital platforms